Antitrust law economic theory and common law evolution - Hylton, Keith N. 1960- (Cambridge University Press, 2003)
This book is an effort to consolidate several different perspectives on antitrust law. First, Professor Hylton presents a detailed description of the law as it has developed through numerous judicial opinions. Second, the author presents detailed economic critiques of the judicial opinions, drawing heavily on the literature in law and economics journals. Third, Professor Hylton integrates a jurisprudential perspective into the analysis that looks at antitrust as a vibrant field of common law. This last perspective leads the author to address issues of certainty, stability, and predictability in antitrust law, and to examine the pressures shaping its evolution. The combination of these three perspectives offers something new to every student of antitrust law. Specific topics covered include perfect competition versus monopoly, enforcement, cartels, section 1 doctrine, rule of reason, agreement, boycott, power, vertical restraints, tying and exclusive dealing, horizontal mergers, and conglomerates